Development of Low Power Converter Solar-Base System - Farhat, Mohamed Agribi (2001)
With the recurrent oil crises and the new environmental boundary conditions for energy production and use, the photovoltaic, PV, system development can be a very promising strategic solution, which releases together with the photovoltaic energy cost effectiveness goal, an actual clean, renewable, and alternative energy option. However, the continues decline in photovoltaic module prices in the international market gives more attention to design the supplementary equipment with low cost and high reliability, such as battery charger and DC-to-AC inverter. The objective of this project is study the effect of irradiation and temperature on the output of solar module and to design, construct, and test battery charger and DC-to-AC inverter for stand alone system. The proposed stand-alone system consists of 5 solar panels, a battery charger, a sealed lead acid battery, a DC-to-AC inverter, and AC loads. The solar energy has been converted to an electric energy using a panel of photovoltaic cells. The electric energy stored in a sealed lead acid battery 30Ah, 12V. The storage process was controlled by an electronic charger, which has been designed and developed for this purpose. A low cost, PWM inverter has been designed and constructed using power BJT switches and electronic components that are common and cheap to convert the stored DC energy to an AC one, and to provide the AC voltage for a small and medium AC loads. Both charging and discharging of the stored energies have been examined, and good results have been obtained. Results of the experimental and simulation work showed that there was a good agreement between the hardware and software. This indicated that the proposed standalone system was successfully developed.